Neurovisceral regulatory circuits of affective resilience in youth - Koenig, Julian (Psychophysiology, 2020)
In an attempt to further elaborate on the Neurovisceral Integration Model, potential developmental trajectories underlying dynamic CNS-ANS co-regulation are presented. In brief, it is suggested that ...
First published: 19 March 2020
Gesehen am 11.01.2022